2020
DOI: 10.1101/2020.04.24.059394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The DMCdrive: practical 3D-printable micro-drive system for reliable chronic multi-tetrode recording and optogenetic application in freely behaving rodents

Abstract: Electrophysiological recording and optogenetic control of neuronal activity in behaving animals have been integral to the elucidation of how neurons and circuits modulate network activity in the encoding and causation of behavior. However, most current electrophysiological methods require substantial economical investments and prior expertise. Further, the inclusion of optogenetics with electrophysiological recordings in freely moving animals remains a general challenge. Expansion of the technological repertoi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…The recording site of each tetrode is confirmed using post-hoc histological analysis (Figure 1D). We found that the single unit activity was relatively stable during one week, two weeks, and two months of recordings after implantation (Figure 1F, G), which is consistent with previously reported chronic tetrode recordings in mice (Tolias et al, 2007;Hong and Lieber, 2019;Kim, Brünner and Carlén, 2020;Voigts et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…The recording site of each tetrode is confirmed using post-hoc histological analysis (Figure 1D). We found that the single unit activity was relatively stable during one week, two weeks, and two months of recordings after implantation (Figure 1F, G), which is consistent with previously reported chronic tetrode recordings in mice (Tolias et al, 2007;Hong and Lieber, 2019;Kim, Brünner and Carlén, 2020;Voigts et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…The recording site of each tetrode is confirmed using post-hoc histological analysis (Figure 1D). We found that the single unit activity was relatively stable during one week, two weeks, and two months of recordings after implantation (Figure 1F, G), which is consistent with previously reported chronic tetrode recordings in mice (Tolias et al, 2007;Hong and Lieber, 2019;Kim, Brünner and Carlén, 2020;Voigts et al, 2020). We implanted a total of 29 tetrodes in the midbrain, hippocampus, thalamus, striatum, and cortex of 14 mice, and recorded the activity of 110 neurons with simultaneous mesoscale cortical imaging for up to 2 months after implantation (Figure 2).…”
Section: Chronic Single-unit Recording With Wide-field Transcranial I...supporting
confidence: 91%
“…PV-Cre mice were used as controls. To allow for lightactivation and identification of the activity of mPFC PV interneurons in the electrophysiological recordings (opto-tagging; Kim et al, 2016Kim et al, , 2020, an adeno-associated virus (AAV) vector with Credependent expression of channelrhodopsin-2 (ChR2) fused to mCherry (AAV-DIO-ChR2-mCherry) was unilaterally targeted to the mPFC (Cardin et al, 2009) (PV-Cre/NR1f/f, n = 3, PV-Cre, n = 4; Figs.…”
Section: Resultsmentioning
confidence: 99%
“…As our LFP analyses indicated increased neuronal firing and altered state transitions in mice lacking NMDAR activity in PV neurons, our next investigations focused on single unit activities during DOWN to UP transitions. As before (Kim et al, 2016(Kim et al, , 2020, we used opto-tagging to identify the activity of PV interneurons in PV-Cre and PV-Cre/NR1f/f mice injected with AAV-DIO-ChR2-mCherry (Figs.…”
Section: Temporal Dynamics Of Mpfc Pv Interneurons and Excitatory Neumentioning
confidence: 99%